EFEKTIVITAS PENERAPAN PEMBELAJARAN BERDIFERENSIASI DALAM MENINGKATKAN HASIL BELAJAR EKONOMI SISWA KELAS X SMA NEGERI 1 MEDAN - Irma Chintia Simbolon; Ainul Mardhiyah (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: This study aimed to determine the differences in learning outcomes between students taught using differentiated learning and those taught using conventional learning, as well as to examine the effectiveness of differentiated learning in improving Economics learning outcomes of tenth-grade students at SMA Negeri 1 Medan. This research employed an experimental method with a quantitative approach. The sample consisted of 72 students divided into an experimental class and a control class. Data were collected through pre-test and post-test assessments. The data were analyzed using the independent sample t-test, ANOVA, and N-Gain test. The results showed a significant difference in learning outcomes between students who received differentiated learning and those who received conventional learning. This was evidenced by the t-value of 13.998, which was higher than the t-table value of 1.994. Furthermore, the N-Gain test result showed a percentage of 78.59%, which was categorized as effective. Therefore, differentiated learning was proven to be effective in improving the Economics learning outcomes of tenth-grade students at SMA Negeri 1 Medan, particularly on the topics of Central Banking, Payment Systems, and Payment Instruments. Keywords: Differentiated Learning and Learning Outcomes   Abstrak: Penelitian ini bertujuan untuk mengetahui perbedaan hasil belajar peserta didik yang menggunakan pembelajaran berdiferensiasi dan pembelajaran konvensional serta mengetahui efektivitas pembelajaran berdiferensiasi dalam meningkatkan hasil belajar Ekonomi siswa kelas X SMA Negeri 1 Medan. Penelitian ini menggunakan metode eksperimen dengan pendekatan kuantitatif. Sampel penelitian terdiri dari 72 siswa yang dibagi ke dalam kelas eksperimen dan kelas kontrol. Teknik pengumpulan data menggunakan tes pre-test dan post-test. Analisis data dilakukan dengan uji t-test, ANOVA, dan N-Gain. Hasil penelitian menunjukkan bahwa terdapat perbedaan yang signifikan antara hasil belajar siswa yang mengikuti pembelajaran berdiferensiasi dan pembelajaran konvensional. Hal ini dibuktikan dengan nilai t-hitung sebesar 13,998 lebih besar dari t-tabel sebesar 1,994. Hasil uji N-Gain menunjukkan persentase sebesar 78,59% yang termasuk dalam kategori efektif. Dengan demikian, pembelajaran berdiferensiasi efektif dalam meningkatkan hasil belajar Ekonomi siswa kelas X SMA Negeri 1 Medan pada materi Bank Sentral, Sistem Pembayaran, dan Alat Pembayaran. Kata Kunci: Pembelajaran Berdiferensiasi dan Hasil Belajar